THE ROLE OF INNOVATIONS IN LEARNING NEW LANGUAGES - Aripova, Kamola; Akramjonova , Muhlisa (University Research Base, 2025)
This article examines the impact of modern technologies and innovative methodologies on language learning processes. As globalization increases the demand for multilingualism, the importance of effective language learning strategies becomes more pronounced. Innovations such as mobile applications, virtual reality (VR), artificial intelligence (AI), and gamified learning experiences play a significant role in enhancing learners' motivation and improving learning outcomes. The article also discusses challenges related to equitable access to technology, the impact on different learning styles, and data privacy concerns.